Efek Antifungi Seduhan Teh Hijau (Camellia sinensis L.) terhadap Pertumbuhan Candida albicans In Vitro - Irene Ardiani Pramudya Wardhani; Sri Haryati; Novan Adi Setyawan (Nexus Biomedika, 2012)
Background : Brewed green tea contains antifungal substance such as polyphenol which is considered can inhibit fungal growth. The aim of this research is to determine antifungal effect of brewed green tea (Camellia sinensis L.) against Candida albicans growth In Vitro. Methods : The research was performed as experimental laboratory. The subject of this research were clinical sample of Candida albicans and taken randomly. This research used 7 treatment groups, they were sterilized aquadest as negative control, brewed green tea with concentration of 60%, 70%, 80%, 90% and 100%, also fluconazole 25 g as positive control. This research was repeated four times. The plate was incubated at the temperature of 37C for 48 hours then inhibition diameter zone formed was measured. The data was analyzed by Linier Regression test then continued by Correlation test on IBM Statistics for Windows version 20. Results : The diameter of inhibition zone increased along with increasing concentrations, because higher concentration of brewed green tea contained more substances, and the diameter of concentration of 100% group is almost the same with diameter of positive control group. The results of statistical analysis using Linier Regression test showed that there are significant differences on seven of treatment groups (p < 0,05) and the Correlation test showed that there are close relation between concentration of brewed green tea and the diameter of inhibition zone. Conclusion : Brewed green tea (Camellia sinensis L.) has antifungal effect against Candida albicans growth In Vitro. Start from concentration of 60% up to 100%, there were antifungal effect, and the antifungal effect of concentration of 100% is close to fluconazole 25 g/ml. Keywords : Antifungal Effect, Brewed Green Tea, Candida albicans